PARTIAL HYDATIDIFORM MOLE ALONG WITH TERM GESTATION AND ALIVE BABY - Parveen, Zahida; Bashir, Rubina; Jadoon, Taimur; Qayum, Iftikhar (Journal of Ayub Medical College Abbottabad, 2004)
Gestational trophoblastic disease consists of a broad spectrum of conditions ranging from an uncomplicated partial hydatidiform molar pregnancy to stage-IV choriocarinoma with cerebral metastases. We describe a partial molar change in the placenta that was associated with a normal female fetus that was delivered at term and is alive and healthy.